The Role of Paradoxical Leadership Behaviors in Promoting Sustainable Organizational Performance (Beacon: International Journal of Education and Social Studies, 2025)
This study aims to examine the role of paradoxical leadership behaviors in promoting sustainable organizational performance. Using a quantitative survey approach, data were collected from 351 respondents, including department heads and academic staff in higher education institutions. Paradoxical leadership behaviors were measured through five dimensions: treating subordinates uniformly while allowing individualization, combining self-centeredness with other-centeredness, maintaining decision control while allowing autonomy, enforcing work requirements while allowing flexibility, and maintaining both distance and closeness. Sustainable organizational performance was assessed through economic, social, and environmental dimensions. Data were analyzed using descriptive statistics and regression analysis. The findings revealed that all dimensions of paradoxical leadership behaviors have a positive and significant effect on sustainable organizational performance. Furthermore, paradoxical leadership behaviors emerged as a strong predictor, explaining 84.7% of the variance in sustainable organizational performance. These results indicate that leaders who effectively balance competing and contradictory demands are better positioned to enhance organizational sustainability by simultaneously improving economic, social, and environmental performance.